Scratch-based Game Design of KaKu to Improve Students’ Ability in Distinguishing Indonesian Formal Words at Primary School - Linda Rahma Dhani Saputri; Tutut Septia Wati; Cahyo Hasanudin; Ayu Fitrianingsih (International Journal of Educational Evaluation and Policy Analysis, 2025)
Formal words are words which follow the language rules that have been determined in formal situations both in oral and written. The purpose of this study is to improve the ability of primary school students in distinguishing formal words. The method used is SDLC (System Development Life Cycle) in waterfall model. The result of this study is the design of a scratch-based game design of KaKu to improve students’ ability to distinguish formal words at primary school has code blocks on 1) Teacher’s sprite, 2) Easy quiz, 3) Medium quiz, 4) Hard quiz, 5) Tick sprite, 6) Cross sprite, 7) Easy sprite, 8) Medium sprite, and 9) Hard sprite. The conclusion of this study is that there are 9 scratch-based game designs of KaKu (formal words) to improve students’ ability to distinguish formal words at primary school.